SINEKDOHA, O‘XSHATISH VA KINOYA: ULARNING BADIIY VA IFODA VOSITASI SIFATIDAGI O‘ZARO BOG‘LIQLIGI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the interrelation of synecdoche, simile, and irony as artistic and expressive devices in literary texts. All three serve an essential role in enhancing imagery, semantic depth, and the author’s aesthetic intention. The study examines synecdoche as a device expressing a whole through a part or a part through a whole; simile as a means of creating vivid imagery through comparison; and irony as a tool that conveys hidden meanings and authorial attitude. The interconnection of these stylistic devices enhances the expressive power of literary language, intensifies its aesthetic impact, and reveals deeper layers of meaning in the reader’s perception